Modular integration of a class of exponetial functions - A. A. Smirnov; V. V. Bondary; P. A. Sahnyuk (Наука. Инновации. Технологии, 2022)
In a paper to inspect the problem of calculation of a modular integral from a class of exponential functions is considered. The basic formula for account of a modular integral is introduced. The example of account of a modular integral is indicated. The consideration of this problem is caused by necessity of processing of signals in unitem number systems. The given direction of researches is considered perspective because there is a possibility to increase produc-tivity of computing systems.